Crack Initiation, Propagation, and Coalescence Experiments in Sandstone Brazilian Disks Containing Pre-Existing Flaws - Shijun Zhao; Qing Zhang; Limin Liu (Advances in Civil Engineering)
This study aims to investigate the fracture behaviors of cracks and crack systems in Brazilian disk (BD) sandstone specimens under compressive line loading. We conduct a series of rock fracture experiments to investigate crack initiation, propagation, and coalescence in samples with one or more pre-existing flaws under radial compressive stress. The displacements and failure loads of the tested specimens are measured. Experimental results show that there are two main types of cracks growing from the pre-existing flaws: wing cracks and secondary cracks. Both initiate mostly from the tips of the pre-existing flaws and propagate in a stable manner. The results reveal that wing cracks appear first and propagate toward the loading direction. Secondary cracks can form in some multiple pre-cracked cases after wing cracks are already present. We also provide a characterization of the observed crack propagation paths and patterns and discuss the influence of pre-existing crack or crack systems. The results help in investigating the failure mechanisms and mechanical properties of rock or rock-like materials.